(untitled) (Al-Academy, 2024)
Research summary: The current research dealt with: (aesthetic composition systems of writings and texts in contemporary Arab sculpture), a number of basic ideas that represent the theoretical material to explain the phenomenon of writing in art in general and in sculpture art in particular, and to reveal aesthetic composition systems and their various types by examining some visual texts of contemporary Arab artists. This research came in four chapters. The first chapter is devoted to: the methodological framework of the research to explain the problem of the research, its importance, the aim of the research, then the limits of the objective, spatial and temporal research, which were determined by the carvings with calligraphic forms executed in the Arab region, then defining the terminology. As for the second chapter: the theoretical framework of the research, it included three sections, the first of which was devoted and tagged: the aesthetic concept of writing, to study the concept of writing in all its theoretical aspects. As for the third topic, tagged: Types of aesthetic formations in the art of sculpture, four points were studied: 1.Circular and spherical aesthetic formation, 2.Horizontal and transverse aesthetic formation, 3.Longitudinal and vertical aesthetic formation, 4.Hierarchical and triangular aesthetic formation. As for the third chapter: the procedural framework for the research, it included the research community and its sample consisting of three artworks by the artist Iyad Al-Husseini. As for the fourth chapter: the results of the research, it was devoted to the results of the research that he reached. The chapter also included a number of recommendations and suggestions.